INVESTIGATION OF PHENOMENA RELATED TO THE UPPER AND LOWER SEMANTIC LEVELS OF THE LITERARY TEXT - M. Gaziyeva (Modern American Journals, 2025)
This article explores the dual-layered semantic structure of literary texts, focusing on the relationship between explicit (upper-level) and implicit (lower-level) meanings within modern Uzbek linguistics. Drawing on the anthropocentric paradigm, the study analyzes how linguistic, cognitive, and pragmatic factors shape textual interpretation. The research highlights that explicit meanings are realized through propositional, modal, and nominative structures, while implicit meanings—manifested through presupposition, secondary meaning, inference, and allusion—form the covert dimension of textual communication. The parallel operation of these layers constitutes a defining feature of artistic discourse, particularly evident in the Uzbek askiya genre. Through a system-structural and intertextual analysis, the study proposes a unified model for differentiating semantic levels and demonstrates how implicit meanings contribute to the aesthetic completeness and cognitive depth of literary texts.
Keywords: Semantic structure, explicit and implicit meaning, propositional structure, presupposition, secondary meaning, inference, allusion, anthropocentric linguistics, askiya genre, intertextuality.